Differential activation of neuropeptide FF receptors by gonadotropin-inhibitory hormone peptides in the European sea bass - Wang, Bin; Paullada-Salmerón, José A.; Vergès-Castillo, Alba; Muñoz-Cueto, José A. (Frontiers in Marine Science, 2023)
Neuropeptide FF (NPFF) and gonadotropin-inhibitory hormone (GnIH) are thought to be paralogous, and a recent study has revealed that both NPFF and GnIH peptides can activate the GnIH receptor (GnIHR, also called NPFFR1) in the European sea bass (Dicentrarchus labrax). However, whether GnIH can bind to the NPFF receptor (NPFFR2) is still yet unknown in this species. Accordingly, we further investigated the potential interactions between GnIH and NPFFR2 (two NPFFR2 forms present in sea bass, namely NPFFR2-1 and NPFFR2-2) on the intracellular signaling pathways.Neither GnIH1 nor GnIH2 had any effect on basal CRE-luc activity, while forskolinstimulated CRE-luc activity was significantly reduced when COS-7 cells expressing sea bass NPFFR2-1 and NPFFR2-2 were challenged with these two GnIH peptides.NPFF and NPAF also inhibited forskolin-induced CRE-luc activity via their cognate receptors. An evident stimulation of SRE-luc activity was observed when COS-7 cells transfected with NPFFR2-1 and NPFFR2-2 were treated with NPFF and NPAF, whereas GnIH peptides had no effect, except a slight but significant increase elicited by 1000 nM of GnIH1 in COS-7 cells expressing NPFFR2-2. Moreover, only GnIH2 exerted an inhibitory action on NFAT-RE-luc activity in COS-7 cells expressing NPFFR2-1. None of GnIH or NPFF peptides altered ERK phosphorylation levels via NPFFR2 receptors. Our results provide new evidence that sea bass GnIH peptides may exert their functions partially via NPFFR2, and PKA, PKC and Ca 2+ routes are potential mediators.